Mutations in the C‐Terminal Domain of ColQ in Endplate Acetylcholinesterase Deficiency Compromise ColQ–MuSK Interaction. Issue 7 (19th April 2013) - Nakata, Tomohiko; Ito, Mikako; Azuma, Yoshiteru; Otsuka, Kenji; Noguchi, Yoichiro; Komaki, Hirofumi; Okumura, Akihisa; Shiraishi, Kazuhiro; Masuda, Akio; Natsume, Jun; Kojima, Seiji; Ohno, Kinji
<x xml:space="preserve">Abstract</x> Missense mutations in COLQ encoding collagen Q (ColQ) compromise binding of ColQ to MuSK and lead to endplate acetylcholinesterase (AChE) deficiency. Defective binding has been proven by an in vitro overlay assay of mutant ColQ on skeletal muscle of Colq‐/‐ mice and by an in vitro plate‐binding assay on purified MuSK. We also confirmed that AAV8‐mediated gene transfer of mutant ColQ into Colq‐/‐ mice failed to express ColQ at the neuromuscular junction and to improve the motor deficits. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>